Double central ray amputation of the third and fourth digits for recurrent giant cell tumors of the hand: A case report. (March 2021) - Johan, Muhammad Phetrus; Nelwan, Dario Agustino; Purnama, Imeldy Prihatni; Nong, Ira; Yudha, Khrisna; Paundanan, Vicky William
Highlights: Recurrent giant cell tumor of bone of hand treated by double central ray amputation. Double central ray amputation results in acceptable functional outcome of the hand. Double ray amputation aims to decrease re-recurrence rates of recurrent GCT of hand. Abstract: Introduction and importance: Recurrent giant cell tumor of the bone (GCTB) of the hand is very rare to be encountered. Our aim is to alert the surgeons to such condition and double central ray amputation of the third and fourth digits could be an option which may reduce the chance of a re-recurrence and provide an acceptable functional outcome. Case presentation: We presented a 25-year-old woman with a recurrent GCTB of the proximal phalanx of the middle finger of the right hand. Considering the recurrent case, a high suspicion of malignancy, and apparent soft tissue extension, the lesion was treated with double central ray amputation of the third and fourth digits through metacarpals. Clinical discussion: Extraosseous soft tissue invasion of recurrent GCTB of the hand had an important role in the treatment recommendation. A balance must be considered between the risk of re-recurrence and the impact of radical resection on function. Double central ray amputation surgery was performed in order to decrease the risk of additional recurrences. Acceptable functionality of the hand as she scored 26/30 (86 % rating) evaluated by Musculoskeletal Tumor Society (MSTS) Scoring System and no signs of local re-recurrence were found for 6 months follow up. Conclusion: Double central ray amputation of the third and fourth digits is a good option for management of recurrent GCTB of proximal phalanx of the third digits with gross soft tissue extension to adjacent fourth digits region.